PROBLEM PENDIDIKAN ISLAM DI ERA GLOBALISASI - Achadah, Alif (INCARE, International Journal of Educational Resources, 2022)
Education is one of most important thing for human live. It also becomes a development benchmark and human change. The higher education taken by people usually influences his perspective and the way to behaves. When a person’s education is higher, he should have a high level of justice and wisdom whether against himself or around him. The development of period has an impact on the existence of globalization which affects to the development in the economic, social, cultural and political fields. The existence of the globalization era certainly has a significant impact on the behavior and relationships of humans. Something that can be a fence of it is knowledge about islamic education and faith of himself. Therefore, there needs to be an analysis between islamic education and globalization.